National Examination and The Quality of Education in Indonesia - Alhadza, Abdullah; M, Zulkifli (Advances in Social Sciences Research Journal, 2017)
This article aims to answer one major question: is the national examination still needed and effective as a tool of educational quality assurance in Indonesia? To answer the question, I employ historical analysis, field observation, and interview techniques. I conclude that the national examination is still needed whether as a tool of educational quality assurance, and as an instrument to maintain the unity of the country.